Stressful Conditions Increase Fatigue during Undergoing Hemodialysis - Sulistini, Rumentalia; Pratama, Yudha; Febriani, Indra; Susanti, Eva; Erman, Imelda (Jurnal Keperawatan, 2024)
Hemodialysis is a therapy given to replace kidney function. This therapy has various physical and psychological impacts on the sufferers. This study aims to analyze stress conditions with fatigue in patients undergoing hemodialysis. Analytic observation research design with a cross-sectional approach. Population of chronic renal failure patients undergoing hemodialysis. The sample was 54 patients, with a non-random sampling technique, with inclusion criteria, namely routine hemodialysis 2 times/week, full consciousness, communication well, and not experiencing complications during dialysis. Analysis using the Independent T-test and Pearson Correlation Test. The instruments used were the Depression Anxiety Stress Scale questionnaire and the fatigue questionnaire. The analysis results obtained the youngest age (17 people), more women than men, most of them have higher education and most of them undergo hemodialysis for more than 11 months. The average patient undergoing hemodialysis experienced mild stress and was in a state of severe fatigue. There was a significant relationship between stress and fatigue (p-value 0.048), with a prediction model that increasing one stress score will increase the fatigue score by 0.237. Therefore, psychological aspects must be an important concern in providing nursing care to patients undergoing hemodialysis in the hemodialysis unit.